Thermal Inactivation of Escherichia Phage OSYSP and Host Strain Escherichia coli O157:H7 EDL933: A Comparative Kinetic Analysis - Mustafa Yesil; David R. Kasler; En Huang; Ahmed E. Yousef (Journal of Food Protection, 2024)
Lytic bacteriophages are promising biocontrol agents against pathogenic bacteria for food and therapeutic applications. Investigating the feasibility of combining phage and physical lethal agents, such as heat, as an effective hurdle combination could lead to beneficial applications. The current research was initiated to compare the thermal inactivation kinetics of a lytic phage (Escherichia phage OSYSP) and its host (Shiga toxin-producing Escherichia coli O157:H7 EDL933), considering they have different critical thermal targets in their structures. To provide a basis for comparison, thermal inactivation kinetics were determined on suspensions of these agents in buffered peptone water using a thermally controlled circulating water bath. Results showed that the bacteriophage virions have a remarkable heat resistance (p < 0.05) compared to their host cells. The D-values of the populations of phage (PFU/mL) and EDL933 strain (CFU/mL) were 166.7 and 7.3 min at 55°C, compared to 44.4 and 0.3 min at 60°C, respectively. Additionally, D-values were significantly (p < 0.05) more influenced by temperature changes in the case of E. coli O157:H7 EDL933 (z-value 3.7°C) compared to that for phage OSYSP (z-value 7.7°C). When the phage suspension was heat-treated in a thermal cycler instead of a water bath, no significant differences between the two treatment procedures (p > 0.05) in estimating virus D- and z-values were observed. Based on these findings, it may be feasible to combine phage OSYSP with mild heat during processing of food to selectively inactivate E. coli O157:H7 EDL933 and subsequently maintain product safety during storage by the surviving phage population; however, the feasibility of this application needs to be investigated. Additionally, the relatively heat-resistant phage OSYSP could qualify as a biological indicator to validate thermal treatments of minimally processed foods in which E. coli O157:H7 EDL933 is the pathogen-of-concern.